2005
DOI: 10.1021/ma047636l
|View full text |Cite
|
Sign up to set email alerts
|

Precision Synthesis of a Fluorinated Polyhedral Oligomeric Silsesquioxane-Terminated Polymer and Surface Characterization of Its Blend Film with Poly(methyl methacrylate)

Abstract: Incompletely condensed, fluorinated polyhedral oligomeric silsesquioxane with the highly reactive group of trisodium silanolate was used for the synthesis of an initiator for atom transfer radical polymerization. The initiator was applied to solution polymerization of methyl methacrylate (MMA) in the presence of a copper complex. The polymerization proceeded in a living fashion, providing tadpole-shaped polymers with an “inorganic head” of polyhedral oligomeric silsesquioxane (POSS) and an “organic tail” of we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 51 publications
5
96
0
1
Order By: Relevance
“…The POSS portion combines the features of organosilicon compounds and possess low free energy (Youngblood and McCarthy, 1999). Thus, the enrichment of the POSS portion at the surface could occur upon incorporating the organicinorganic amphiphile into organic polymer and the surface hydrophobicity of materials will significantly be enhanced (Koh, 2005). Hence, the hydrophobic part of POSS was chosen to study the effect of POSS on surface morphology of polymers and thereby influencing the permeability and selectivity of gases.…”
Section: Structure -Property Relationships 141 Morphology Effect Onmentioning
confidence: 99%
“…The POSS portion combines the features of organosilicon compounds and possess low free energy (Youngblood and McCarthy, 1999). Thus, the enrichment of the POSS portion at the surface could occur upon incorporating the organicinorganic amphiphile into organic polymer and the surface hydrophobicity of materials will significantly be enhanced (Koh, 2005). Hence, the hydrophobic part of POSS was chosen to study the effect of POSS on surface morphology of polymers and thereby influencing the permeability and selectivity of gases.…”
Section: Structure -Property Relationships 141 Morphology Effect Onmentioning
confidence: 99%
“…Subsequently, a variety of POSS-based small molecules or polymers were synthesized and the different self-assembly behavior was achieved as well [8][9][10][11][12]. Wamke et al [13] successfully synthesized two open-cage TSiO-POSS and DSiB-POSS with short alkyl chains and compared the interfacial property of Langmuir monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…13 From the standpoint of molecular design, the organic and inorganic phases are combined with covalent bond to form POSS, is a new type of organic-inorganic hybrid material. [14][15][16][17][18][19][20][21][22][23][24] It is reported that POSS exists in the following structures: random, ladder, cage, and partial cage. 25,26 POSS can be incorporated into polyurethanes by physical blending and chemical modifications.…”
Section: Introductionmentioning
confidence: 99%